Analysis Of The Additional Value Of Education In The Micro And Macro Dimensions - Muhammad Alfian; Kasful Anwar US; As'ad Isma (Cita konsultindo, 2023)
Education is actually an activity that aims to glorify and humanize humans. The existence of education is an important element in responding to the challenges of life in this modern era, in order to establish human existence itself. The additional value of education in terms of macro and micro elements, is intended as the extent to which this education is transformed as a tool that makes humans more competent individuals, as well as confirms their position to be efficient in society. Education in the macro and micro dimensions is inseparable from the financing of education and improving the quality of education, in a broad scope covering education in a country, as well as in a narrow sense covering financing and improving the quality of education in a particular educational institution.